Silver-Containing Thin Films on Transparent Polymer Foils for Antimicrobial Applications - Vitelaru C. Catalin; Parau A. C. Anca Constantina; Kiss A. E. Adrian; Pana I. Iulian; Dinu M. Mihaela; Constantin L. R. Lidia; Vladesku A. Alina; Tonofrei L. E. Lavinia; Adochite C. S. Cristina; Costinas S. Sarah; Rogozea L. Liliana; Badea M. Mihaela; et al. (2022, 2022)
Title screen